Burnout Pada Perawat Di RSU Daerah: Apa Penyebabnya? - Kusuma Wardani, Riastuti; Salsabila Putri Alawiansyah; Hida Nurrizka, Rahmah; Ariyanti, Fajar (Journal of Religion and Public Health, 2025)
Background: Burnout is a condition of physical, emotional, and mental exhaustion caused by high work pressure, often experienced by healthcare workers such as nurses. Nurses at the Depok regional government hospitals experienced the highest burnout rates found in the ICU unit at 40%. Objective: This study aims to identify the factors associated with burnout among nurses at RSUD Kota X, West Java Province, in 2024. Methods: This research is a quantitative study with a cross-sectional design involving 84 respondents selected using random sampling techniques. Results: Nurses working at RSUD Kota X, West Java Province, experienced moderate burnout at a rate of 56.3%, while 41.7% experienced low burnout. Factors associated with burnout among nurses include age (P-value = 0.035), gender (P-value = 0.019), job control (p-value = 0.037), workplace recognition (p-value = 0.036), and social support (p-value = 0.039). Conclusion: Age, gender, job control, workplace recognition, and social support are significantly associated with burnout among nurses at RSUD Kota X, West Java Province, in 2024. Nurses are encouraged to manage stress by thinking positively, engaging in hobbies, and supporting one another to prevent burnout. Keywords: Burnout, Nurses, District Hospitals.